2006
DOI: 10.1007/s10350-005-0281-8
|View full text |Cite
|
Sign up to set email alerts
|

First 100 Cases With Doppler-Guided Hemorrhoidal Artery Ligation

Abstract: Our experience indicates that Doppler-guided hemorrhoidal artery ligation is safe and effective and can be performed as an outpatient procedure with local or regional anesthesia and with minimal postoperative pain and early recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 20 publications
6
42
0
4
Order By: Relevance
“…which was structurally similar to our study (1 (11,12). In another study, the results of DGHAL alone proved to be satisfactory (13).…”
Section: Discussionsupporting
confidence: 73%
“…which was structurally similar to our study (1 (11,12). In another study, the results of DGHAL alone proved to be satisfactory (13).…”
Section: Discussionsupporting
confidence: 73%
“…However, about 40% were reported to have recurrent hemorrhoidal piles. Greenberg et al [16] report 89% asymptomatic patients and an 11% re-treatment rate after 1 year follow-up. A randomized trial comparing hemorrhoidectomy and DG-HAL found no difference between recurrence rates in preoperative symptoms at 1 year follow-up [17].…”
Section: Discussionmentioning
confidence: 99%
“…22,103,104 However, there are no good data on the learning curve and the steps that are required to achieve competence. The existence of a learning curve has been alluded to.…”
Section: Learning Curvementioning
confidence: 99%